2018
DOI: 10.1002/chem.201706088
|View full text |Cite
|
Sign up to set email alerts
|

Deracemization of a Racemic Compound by Using Tailor‐Made Additives

Abstract: Viedma ripening is a process that combines abrasive grinding of a slurry of crystals with solution-phase racemization, resulting in solid-phase deracemization. One of the major disadvantages of Viedma ripening is that the desired compound needs to crystallize as a racemic conglomerate, accounting for only 5-10 % of all chiral molecules. Herein, we show that use of a chiral additive causes deracemization under conditions, in which the compound normally crystallizes as a racemic compound. Although this concerns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The low productivity of TCID is obviously due to the associated long process times. Indeed, the usual minimum process duration for TCID is about 10 h. 7,8,16,17 In contrast, PC runs typically involve rapid cooling; thus, the process times are much shorter. It is therefore important to shorten process times to significantly improve the process productivities and achieve a process with high productivity.…”
Section: Introductionmentioning
confidence: 99%
“…The low productivity of TCID is obviously due to the associated long process times. Indeed, the usual minimum process duration for TCID is about 10 h. 7,8,16,17 In contrast, PC runs typically involve rapid cooling; thus, the process times are much shorter. It is therefore important to shorten process times to significantly improve the process productivities and achieve a process with high productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Any composition in undersaturated or saturated solutions will evolve towards the racemic composition because of racemization in the liquid phase. There have been many reports on the irreversible evolution to a single chirality in the solid state for racemizable conglomerate‐forming systems . As long as the system remains an undersaturated solution, the enantiomeric excess of the system remains zero.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the prerequisite for a racemization step is a major limiting factor for applying Viedma ripening, and many attempts were made to overcome this bottleneck. Successful that resulted in complete deracemization were made through the combination of grinding with physical factors, such as temperature gradients [123], temperature cycling [124], chiral additives [125], UV-light [126], and continuous solvent exchange, with which the very important antimalaria drug Mefloquine was deracemized [127]. Moreover, Vlieg et al showed that Viedma ripening is also effective for obtaining a single enantiomer, not only for compounds with a single stereocenter, but also from a mixture of stereoisomers with two (or more) different stereocenters, in a process that should be preceded by epimerization of stereocenters, and crystallization of the most stable pair of enantiomers as a racemic conglomerate [128].…”
Section: Crystallization-assisted Chiral Resolution In Solid Phasementioning
confidence: 99%